Expression of human epidermal growth factor receptor 2 in primary and paired parenchymal recurrent and/or metastatic sites of gastric cancer - SHIBATA, RYOSUKE; NIMURA, SATOSHI; HASHIMOTO, TATSUYA; MIYAKE, TORU; TAKENO, SHINSUKE; HOSHINO, SEIICHIRO; NABESHIMA, KAZUKI; YAMASHITA, YUICHI (Molecular and Clinical Oncology, 2014)
Human epidermal growth factor receptor 2 (HER2) status has been evaluated at the primary site of gastric cancer when planning trastuzumab therapy against recurrent or metastatic lesions, since tissue sampling is uncommon in recurrent or metastatic lesions. This study retrospectively investigated the concordance of HER2 expression between primary and metastatic/recurrent lesions in order to confirm sensitivity to trastuzumab. The subjects comprised 37 patients with gastric adenocarcinoma who underwent tissue biopsy or surgical resection of the primary sites and 49 paired synchronous or metachronous metastatic sites (excluding lymph nodes) at the Fukuoka University Hospital between January, 1998 and September, 2012. All the samples were evaluated for HER2 status at the invasive front by immunohistochemistry (IHC). The HER2 positivity rate of the primary sites was ~16% and the concordance ratio of the IHC results between primary and paired metastatic sites was ~97%. No discordant cases regarding HER2 status were found among metachronous interventions for metastatic lesions. Only one patient exhibited conversion from a HER2-negative status in all the portions of the primary site to a positive status in a metastatic site. In conclusion, a high concordance ratio for HER2 status was observed between primary and paired metastatic lesions. Thus, employing trastuzumab therapy against metastatic or recurrent gastric cancer based on the HER2 status of the primary lesion appears to be an acceptable approach.